The Long-Term Forecast of the Russian Tourism Development - Zaitseva, Natalia A.; Kropinova, Elena G.; Korneevets, Valentin S.; Dragileva, Irina I.; Chudnovskiy, Alexey D. (International Review of Management and Marketing, 2016)
The article directs at identifying of the main indicators of the long-term forecast of the Russian tourism development. The authors have applied the methods of extrapolation, expert evaluation, and scenarios, enabled the authors to develop a baseline and target scenarios of tourism development in the Kaliningrad region of Russia. The paper reveals the investigation of macro- and micro-economic factors, affecting the development of tourism in the region today and in the long term perspective. It also proves the measures that may have the greatest influence on the development of tourism in the region in the next 5-10 years. Presented in the article methodology of building the long-term forecast can be useful not only for the Kaliningrad region and the other Russian regions, but also for foreign countries. Article materials are of practical value to state authorities, Russian and foreign investors in determining the prospects of the tourism development in the Kaliningrad region. Keywords: tourism, Kaliningrad region, the regional tourism product, development scenarios, long-term forecast.